Effect of ammonium‐iron‐hexa‐cyanoferrate and of the covariates age, gender, weight, season and calendar time on radiocaesium contamination of wild boars living in the wild in Bavaria. Issue 3 (29th March 2012) - Kienzle, E.; Reddemann, J.; Swart, D.; Swart, A.; Draxler, B.; Morfeld, P.
Summary Feed with Ammonium‐iron‐hexa‐cyanoferrate (AFCF; 1250 mg AFCF/kg) was fed between March 2009 and March 2011 to wild boars in a territory of 4.5 km2 (experimental group, EXP). One hundred and forty similar territories in the same county (500 km2, spruce forest, agriculture) served as control (CON). Data for comparison from all territories were available from March 2005 to March 2011. Wild boars could move between, into and from the territories. Lean skeletal muscle meat (500 g) of all wild boars that were killed by humans (hunting and traffic accidents) was investigated for gamma‐radiation from 137Cs with a becquerel monitor with a sodium iodide scintillator crystal (range of detection 20–9999 Bq/kg). The wild boars were weighed, and gender and age were determined. For the analyses of effects, multivariable regression models were fitted with the 137Cs concentration as response variable. There was a significant difference between the 137Cs contamination of wild boars from CON (563 ± 932 Bq/kg meat, n = 1253) and EXP (236 ± 276 Bq/kg meat; n = 45). 137Cs contamination decreased with increasing body weight by −5 Bq/kg meat/kg body weight increase (p < 0.05). Females had higher Bq measurements than males (by +80 Bq/kg meat, p < 0.05). Piglets were lower than adults, but turn‐coats higher. From November to May, contamination was higher (by +500 to +600 Bq/kg meat, p < 0.05) than during the rest of the year. In 2010, contamination was higher (by +200 to + 300 Bq/kg meat, p < 0.05) in comparison with the other years under observation. When all covariates were controlled for, the effect of AFCF was highly significant. Interaction analyses showed that the intervention decreased 137Cs contamination by −500 Bq/kg meat during November to May and by −200 Bq/kg meat during the rest of the year. In summary, AFCF feeding reduces 137Cs contamination of wild boars living in the wild significantly, particularly during the season from November to May.